OP0006 Distinct mechanisms of il-1 inhibition revealed by in vitro modelling of il-1 receptor accessory protein interactions with il-1/il-1 receptor complex. (1st June 2001) - Varnum, BC; Witte, A; Vezina, C; Qian, X
Abstract : Background: IL-1 stimulates cellular responses by interacting with a heterodimeric receptor complex comprised of IL-1 receptor type I (IL-1RI) and IL-1 receptor accessory protein (IL-1RAcP). IL-1 first binds IL-1RI then IL-1RAcP is recruited to this complex. Inhibitors of IL-1 bioactivity may function through inhibiting any aspect of this complex formation. Understanding the mechanism of inhibition of specific inhibitors can shed light on the nature of the interfaces that define a high affinity site for IL-1RAcP binding. Objectives: To model the interaction of IL-1 Receptor Accessory Protein with IL-1 bound IL-1 Receptor using purified recombinant proteins, and assess the mechanism of antagonism for IL-1 inhibitors. Methods: The extracellular domain of IL-1RAcP was expressed and purified. The interaction of IL-1RAcP with IL-1RI, IL-1 and IL-1RI/IL-1 complex was explored in binding assays. Antibodies to IL-1 and IL-1RI have been used to investigate the roles of individual components of the complex. IL-1 bioassays have been developed to validate the in vitro findings. Results: As expected, IL-1RAcP did not interact with either IL-1 or IL-1RI alone, even at high concentrations (100 nM), however, binding to complex was measured to be high affinity ( 1 nM). Furthermore, purified IL-1RAcP enhanced binding of IL-1 to receptor. Antibodies to IL-1b have been identified which block binding of IL-1/IL-1RI to IL-1RAcP but fail to influence IL-1 binding to receptor. Conclusion: The observation that anti-IL-1beta antibodies can selectively block binding of IL-1RAcP demonstrates a novel mechanism of IL-1 inhibition and supports the hypothesis that IL-1 makes direct contacts with IL-1RAcP. Since IL-1 does not demonstrate any measurable affinity for IL-1RAcP when not bound to IL-1RI, it is likely that additional elements of the binding site are comprised of IL-1RI residues. Future studies mapping the elements of IL-1RAcP involved in the contact points will further define the binding interface.